HUMOUR AS A STYLISTIC AND PRAGMATIC DEVICE IN ENGLISH AND UZBEK LITERATURE - Adizova Madina Komilovna,; Nosirova Dilnoza Rizokulovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. The article comparatively examines humour as a stylistic and pragmatic device in English and Uzbek literature. Theoretical approaches used to look at interaction of humour with other related stylistic and pragmatic device such as irony, satire, sarcasm and wordplay. There were used comparative, stylistic and pragmatic methods,  chosen novels and short stories in the context of English and Uzbek languages were explored. The acquired results reflect common and culture-specific elements in how the humour is used, showing its role in character description and reader’s engagement. Сontribution of the study includes comparative literary studies and supports intercultural communication in the teaching and learning of English and Uzbek literature.